Estimates of the Effects of Emigration on the Labour Market - Kasnauskienė, Gindra; Šiaudvytis, Tomas (Lithuanian Journal of Statistics, 2019)
Migration flows have increased since the EU enlargement in 2004. In many European countries, they are sufficiently large to have significant economic effects. These effects are among the most popular topics in public debate. In this paper, the authors attempt to quantify the effects of emigration on wages, welfare and income redistribution in the selected new EU member states. Emigration reduces labour supply and increases national wage generating income redistribution from the owners of capital to the labour force. Emigration also results in welfare loss as emigrants no longer produce output in their home country. The authors of the article adopt a simple theoretical model of the labour market which allows quantifying these effects through the use of basic economic and demographic statistics. The research on the effects of emigration on wages uses a simple supply and demand framework, where labour demand is derived from a marginal productivity condition using the Cobb–Douglas production function. The authors also assume perfectly inelastic labour supply, in case of which the effect of emigration on wages is entirely determined by labour demand. Wage elasticity estimation uses the fact that the capital share parameter in the Cobb–Douglas function also measures labour demand elasticity. This property of the production function allows the authors to estimate the elasticity using national accounts data. The estimates of labour demand (wage) elasticity for Lithuania range from 0.44 to 0.55, implying that due to emigration wages might have increased from 0.75 to 0.94 per cent a year, on average. In the period of 2001–2008, emigration might have resulted in a wage increase of 5.9 to 7.3 per cent. However, these estimates require caution as the beginning of the period was characterised by high unemployment. Emigration loss amounts to 0.4 per cent of GDP, and 2.8 per cent of GDP is redistributed to labour every year. Due to the poor quality of migration data, the impact of emigration on wages, welfare and income redistribution in other countries is most likely significantly underestimated. The assumption that the share of declared emigration is similar across countries would imply that those affected by emigration the most are Slovenia, Czech Republic and Estonia.